Analisis Pelaksanaan Kode Etik Dalam Praktik Citizen Journalism pada Akun Twitter Tribun Lotto21group - Adam Poetro Yudhonegoro; Zuhri Firdaus Anas (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
The research was initiated in response to the increasing number of violations committed by media organizations, particularly those relating to violations of media ethics rules. Up to 30% of code of conduct violations are committed by online media. The Press Council said the number of news complaints reached more than 500 complaints throughout 2012, 98 of which were related to online media. As many as 76% of complaints related to violations of the Code of Ethics for Journalists. Technological advances along with the rapid development of social media have made it easier for people to disseminate information, ranging from writing, reporting, to disseminating information encountered in everyday life. In creating information, it is necessary to understand the journalistic code of ethics so that the content shared does not cause new conflicts in society. This research was conducted to examine how the Code of Journalistic Ethics is applied to the Twitter account TRIBUN LOTTO21GROUP as a citizen journalism media. This research is a descriptive qualitative research which means describing, presenting, explaining, or answering an existing problem in more detail